Artemídia escrevente: a caligrafia entre a arte e o design - Kondo, Bianca [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The term “writing media art” expresses an artisticscientific process performed in the Art-Science Communication interface presented as Final Paper in Visual Arts baccalaureate modality. The first part gathers, in artistic-scientific research, a historical overview of the relation between image and writing, which its main focus is calligraphy and its different expressions in art and design, including their interrelations. The identification is made from bibliographical and iconographical survey, both printed and virtual materials. This approach involves the selection of authors’ statements and comments in order to offer a deeper historical basis, since it comes to facts and events. The second part relates to the set of works produced during the four-year period of the Visual Arts course, including a reflection about the creation process and all that surrounds it – influences, memories, visions etc. – to finally establish a connection between all these elements in order to make clear this incredible web of creation. This work is inserted in the line of research “Artistic Processes and Procedures” of the Department of Fine Arts of the Art Institute of UNESP and describes: creative process, production and influences. The methodology used was Freinetiana Educational Cybernetics, developed in the research group “Art media and Videoclip”, whose leading advisor is the one from this Final Paper. The result and discussion of the artistic-scientific research were reported in monography in the following versions: PDF File repository for dissemination in the virtual library of the Institute of Arts; hardcover version for physical collection in the Library of the Institute of Arts; paper version for the committee; template version appropriate for submission to International Scientific Congress in the area of Arts

O termo “artemídia escrevente” expressa um processo artístico-científico realizado na interface Arte- Comunicação-Ciência apresentado como Trabalho de Conclusão de Curso em Artes Visuais na modalidade Bacharelado. A primeira parte reúne, na abordagem da pesquisa artístico-científica, um panorama histórico da relação entre imagem e escrita, tendo como principal foco a caligrafia e suas diferentes expressões na arte e no design, envolvendo inclusive suas inter-relações. A identificação é feita a partir de levantamento bibliográfico e iconográfico, tanto de impressos quanto de material virtual. A abordagem envolve a seleção de depoimentos e comentários de autores com o objetivo de oferecer um embasamento histórico mais profundo, já que se trata de fatos e acontecimentos. A segunda parte diz respeito ao conjunto de trabalhos produzidos durante o período de quatro anos do curso de Artes Visuais, incluindo uma reflexão a respeito do processo de criação e tudo o que o envolve – influências, memórias, olhares etc. – para, enfim, estabelecer uma conexão entre todos esses elementos a fim de tornar claro essa incrível rede de criação. O presente trabalho está inserido na linha de pesquisa “Processos e Procedimentos Artísticos” do Departamento de Artes Plásticas do Instituto de Artes da UNESP e descreve: processo criativo, produção e influências. A metodologia utilizada foi a Cibernética Pedagógica Freinetiana, desenvolvida no Grupo de Pesquisa “Artemídia e Videoclip”, do qual é líder o orientador deste Trabalho de Conclusão de Curso. O resultado e a discussão da pesquisa artístico-científica foram relatados em monografia com as seguintes versões: versão em pdf para divulgação em repositório virtual na Biblioteca do Instituto de Artes; versão capa dura para acervo físico na Biblioteca do Instituto de Artes... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Caligrafia; Arte; Mídia; Escrita